KRITIK FEMINIS TERHADAP DEVELOPMENTALISME - Lailiy Muthmainnah (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractFeminist activists made a breakthrough of attempt in reformulating a development theory. The basic issue was breaking the binary logic on the development theory. The feminists try to place gender relation at the center of theorization. To make it more concrete, every feminist movement establish projects and programs to improve the economic and social position of women. It is seen on their program, from Women in Development until Postmodern and Development. Although every feminist movement had a different vision and mission, but we can conclude that almost every critic to development have a similar attention to the androcentricism of science and unfairness on the distribution on material resources that occur on the process of development.Keywords: Feminist activists, gender relation, development.